Modern slavery a reference handbook - Villegas, Christina G. (Contemporary world issues, 2020)
"Modern Slavery provides a thorough treatment of the evolving scope, nature, and contexts of modern slavery and a discussion of prevention and abolition efforts in an accessible format for high school and college readers"--